Correction: A deep hybrid learning pipeline for accurate diagnosis of ovarian cancer based on nuclear morphology - Sengupta, Duhita; Ali, Sk Nishan; Bhattacharya, Aditya; Mustafi, Joy; Mukhopadhyay, Asima; Sengupta, Kaushik (PloS one, 2024)
[This corrects the article DOI: 10.1371/journal.pone.0261181.].